Cow-calf risk management among Kansas producers - Pope, Kelsey Frasier (Kansas State University, 2009)
Considerable risk is present in today’s ranching world; especially price and production risk. A producer who can tolerate more risk, and is knowledgeable about how to effectively manage price and production risk, may have opportunity to increase profitability relative to a highly risk averse producer. The purpose of this study is to investigate perceptions and sources of risk, identify how risk management is conducted, assess price and production risks, and view differences between producers’ perceptions versus their attitudes towards risk and factors that affect risk. In order to investigate cow-calf producers’ perceptions of risk, an instrument was created to survey beef cow-calf producers in the Kansas Farm Management Association (KFMA). Respondents provided information on their production practices, marketing methods, operating decisions and risk related to their cow-calf operations. A risk preference score for individual producers was developed from specific survey questions to determine three objectives: to classify producers’ risk preferences related to their operating decisions; determine operating decisions that affect risk preferences; and identify what production and marketing practices in which producers were willing to risk for a chance to increase the net returns to their operations. A bi-directional causality between risk aversion and operation characteristics was illustrated between how operating decisions are related to risk aversion, and risk aversion is related to operating decisions. Factors that were found to influence risk aversion were socioeconomic factors such as age, off-farm income, debt-to-asset ratio, farm size, and number of cows owned, as well as comparative advantages of producer’s: use and analysis of new technology, business planning skills and marketing skills. Models showing how risk aversion was related to production management focused on producer’s financial soundness, production practices and marketing methods, specific to retained ownership. Producers who would participate in value-added programs to increase returns to their operation have a comparative advantage in marketing skills, own more cattle, and are less diversified in terms of their farm enterprise incomes.
Keywords: cow-calf; risk; production management; Kansas producers; financial risk; survey development; Economics, Agricultural (0503)